Effect of Rehabilitation on Sleep Quality After Ablation for Atrial Fibrillation: Data From a Randomized Trial. Issue 3 (May 2018) - Risom, Signe Stelling; Fevejle Cromhout, Pernille; Overgaard, Dorthe; Hastrup Svendsen, Jesper; Kikkenborg Berg, Selina
Abstract : Background: Low sleep quality is common in patients with atrial fibrillation (AF). Positive effects of cardiac rehabilitation on patients treated for AF with ablation have been found, but whether cardiac rehabilitation affects sleep quality is unknown. The objectives of this study were to investigate (1) differences in sleep quality between cardiac rehabilitation and usual care groups and (2) whether other factors could affect sleep quality. Methods: From the randomized CopenHeartRFA trial, 210 patients treated for AF with ablation were included. A rehabilitation program consisting of physical exercise and psychoeducational consultations was tested. Sleep quality was measured with the Pittsburg Sleep Quality Index (PSQI) questionnaire before intervention and at the end of intervention. Anxiety, depression, and European Heart Rhythm Association scores were assessed. Results: No difference between groups in sleep quality was found (PSQI global mean [SD] score, 6.60 [3.61] points for the cardiac rehabilitation group [n = 83] and 6.08 [3.60] points for the usual care group [n = 90]; P = .34), although improvements in sleep quality were noted in both groups. Sleep latency, duration, and efficiency were significant by type of AF at 1 month. Anxiety, depression, and higher European Heart Rhythm Association scores at 4 months were associated with a higher PSQI global mean score at the end of intervention. Conclusion: The rehabilitation program showed no effect on sleep quality. A large proportion of patients reported poor sleep quality, and patients reporting anxiety, depression, or AF symptoms described worse sleep quality compared with patients who did not experience anxiety, depression, or AF symptoms. More research in the field is warranted.